Analysis of underground transmission cable ampacity for on-site applications / Khairul Ikhwan Rosdi, Norhidayu Rameli and Shahnurriman Abdul Rahman - Rosdi, Khairul Ikhwan; Rameli, Norhidayu; Abdul Rahman, Shahnurriman (UiTM Press, 2024)
Temperature poses a primary concern that must be addressed before installing power cables under the ground. This is due to the temperature increase at greater depths, which can impact the cable’s ampacity. The higher the temperature, the higher the thermal resistance, resulting in a lower ampacity current being transmitted to the consumers, thus affecting electricity services. Therefore, this study aims to analyze the ampacity of underground transmission cables for on-site cable installation, considering different layout buried depths. The 132 kV underground transmission power cable was designed and simulated using COMSOL Multiphysics at varying burial depths for tarmac roads and horizontal direct drilling (HDD), with different conductor sizes. Additionally, the cable was arranged in a trefoil formation within the surrounding surface for both single and double circuits. Finally, the simulation displayed the cable condition, which is the cable’s temperature. Results indicated that the cable temperature increased when the buried depth for the tarmac and HDD layout increased. About 3% of the temperature is increased with the depth of the buried cable. Besides, the cable temperature increased by about 17% when the cable was placed next to each other as a double circuit arrangement. As a result, the ampacity analysis on the underground transmission cable at different layouts and circuits depicts the deeper installation depth, and the closest number of circuits may cause the higher temperature. Hence, this study may provide valuable insight to electrical engineers by offering temperature data before the installation of 132 kV underground power cables in both layouts at a later stage.